Building on the Monterrey consensus : the growing role of public-private partnerships in mobilizing resources for development (Economic World Forum GenevaCH, 2005)
Examines how public-private partnerships (PPPs) can best be harnessed to extend the reach and effectiveness of aid to address international and national development challenges.
Keywords: PARTNERSHIP